Subject of Degree and the Gender Wage Differential Evidence from the UK and Germany - Stephen Machin; Patrick A. Puhani (Institute for the Study of Labor (IZA), 2002)
We show that controlling for subject of degree explains a significant part of the male/female gender wage differential amongst graduates. Using data from the labour force surveys of the United Kingdom and Germany, we find similar results in these two countries: subject of degree explains about 2-4 percent higher wages of male over female graduates after controlling for age, industry, region, part-time and public sector employment. This is a significant part (between 9 to 19 percent) of the overall male/female gender wage gap, and an even larger amount of the part explained by factors entered into wage equations (at around 20 to 29 percent of the explained component).
Keywords: J71; J16; J31; 330; gender wage gap; field of major; Lohndifferenzierung; Geschlecht; Akademische Berufe; Beruf; Frauenarbeitslohn; Schätzung; Deutschland; Großbritannien